2021
DOI: 10.3390/nu13020544
|View full text |Cite
|
Sign up to set email alerts
|

U.S. Montmorency Tart Cherry Juice Decreases Bone Resorption in Women Aged 65–80 Years

Abstract: Pre-clinical studies have demonstrated that tart cherries, rich in hydroxycinnamic acids and anthocyanins, protect against age-related and inflammation-induced bone loss. This study examined how daily consumption of Montmorency tart cherry juice (TC) alters biomarkers of bone metabolism in older women. Healthy women, aged 65–80 years (n = 27), were randomly assigned to consume ~240 mL (8 fl. oz.) of juice once (TC1X) or twice (TC2X) per day for 90 d. Dual-energy x-ray absorptiometry (DXA) scans were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(32 reference statements)
0
6
0
1
Order By: Relevance
“…For example, Chai and colleagues [ 14 ] reported a higher BMI (1.06 kg/m 2 ) in those consuming MC concentrate for 12 weeks. More recently, Dodier et al [ 70 ] reported an increase in body mass and BMI, following the intake of 240 mL/day of MC for 90 days, warranting careful consideration in future research designs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Chai and colleagues [ 14 ] reported a higher BMI (1.06 kg/m 2 ) in those consuming MC concentrate for 12 weeks. More recently, Dodier et al [ 70 ] reported an increase in body mass and BMI, following the intake of 240 mL/day of MC for 90 days, warranting careful consideration in future research designs.…”
Section: Discussionmentioning
confidence: 99%
“… 41 , 42 Postmenopausal women consuming TC juice twice daily exhibited a decrease in the bone resorption marker, tartrate-resistant acid phosphatase type 5b. 43 Phenolic acids reduce osteoclastogenesis by inhibiting the receptor activator of nuclear factor κB (RANKL) and promoting osteoblast differentiation via TGF-β signaling in both bone and gut in a Treg cell differentiation–dependent manner. 42 , 44 However, these phenolic acids are relatively poorly absorbed, which suggests that their effects on bone cells may also be mediated via gut-derived metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bell et al ( 18 ) found a 29% decrease in CRP 5 h after ingestion of 30 or 60 ml MTC concentration, with no difference between the doses, and this reduction was still apparent at 48 h. However, Hillman and Uhranowsky ( 22 ) did not find a change in CRP during a 48 h intervention with either 30 or 60 ml MTC juice. Moreover, a 4 week intervention with MTC juice found a non-significant 19% reduction in CRP ( 23 ), while other interventions lasting 6 weeks ( 39 ) and 12 weeks ( 36 , 40 ) also failed to find significant reductions in CRP from MTC supplementation. Two investigations that utilized sweet Bing cherries did find significant reductions in CRP both after 3 h ( 41 ) and 28 day ( 42 ).…”
Section: Discussionmentioning
confidence: 96%
“…However, because it is an essential marker of inflammation and elevated CRP has been noted in many inflammatory diseases (38) it can be a valuable tool for evaluating the impact of tart cherry on inflammation. (36,40) also failed to find significant reductions in CRP from MTC supplementation. Two investigations that utilized sweet Bing cherries did find significant reductions in CRP both after 3 h (41) and 28 day (42).…”
Section: C-reactive Proteinmentioning
confidence: 95%